2000
DOI: 10.1086/315372
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Drug–ResistantChlamydia trachomatisAssociated with Clinical Treatment Failure

Abstract: In vitro susceptibility testing and genotyping were done on urogenital isolates of Chlamydia trachomatis from 3 patients, 2 of whom showed evidence of clinical treatment failure with azithromycin and one of whom was the wife of a patient. All 3 isolates demonstrated multidrug resistance to doxycycline, azithromycin, and ofloxacin at concentrations >4.0 microg/mL. Recurrent disease due to relapsing infection with the same resistant isolate was documented on the basis of identical genotypes of both organisms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
169
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(174 citation statements)
references
References 35 publications
2
169
0
3
Order By: Relevance
“…Indeed, whereas some organisms, like Chlamydia and Legionella, are quite sensitive, this may not be the case for others, such as S aureus. The importance of a concentration threshold in intracellular activity has been demonstrated recently by the description of clinical failures with Chlamydia showing resistance to concentrations of azithromycin of 4 mg/L or higher in the BGMK cell assay system [87]. Interestingly enough, an increase in azithromycin accumulation, as obtained by inhibiting its efflux from macrophages, has been shown to decrease the extracellular concentration needed to obtain a bacteriostatic affect in the S aureus/J774 macrophage model depicted in Fig.…”
Section: Intracellular Activity Of Antibiotics (Cellular Pharmacodynamentioning
confidence: 88%
“…Indeed, whereas some organisms, like Chlamydia and Legionella, are quite sensitive, this may not be the case for others, such as S aureus. The importance of a concentration threshold in intracellular activity has been demonstrated recently by the description of clinical failures with Chlamydia showing resistance to concentrations of azithromycin of 4 mg/L or higher in the BGMK cell assay system [87]. Interestingly enough, an increase in azithromycin accumulation, as obtained by inhibiting its efflux from macrophages, has been shown to decrease the extracellular concentration needed to obtain a bacteriostatic affect in the S aureus/J774 macrophage model depicted in Fig.…”
Section: Intracellular Activity Of Antibiotics (Cellular Pharmacodynamentioning
confidence: 88%
“…Bacterial growth modification was assessed by IFU assay, fluorescence microscopic analysis and RT-PCR as shown below. Because it is well known that ofloxacin (OFLX) or clarithromycin (CAM) are ineffective against bacteria in the persistent phase [12], these antibiotics were used as an indicator to confirm whether persistent infection occurred due to treatment with IFN.…”
Section: Infectionmentioning
confidence: 99%
“…The presence of C. pneumoniae in persistent infection is characterized by an absence of culturability [7], in addition to altered bacterial RNA and protein levels [8][9][10][11], morphologically altered chlamydial bodies [8] and increased resistance to antimicrobials, such as azithromycin or clarithromycin, frequently used for the treatment of C. pneumoniae infection [12]. The mechanisms leading to persistent C. pneumoniae infection remain unclear; however, infection in reported cases occurred during an uncompleted developmental cycle with a lack of maturation of the EB, and an absence of bacterial metabolic activity caused a decrease in sensitivity to the antibiotics used.…”
Section: Introductionmentioning
confidence: 99%
“…61 There is emerging evidence that C. trachomatis is developing antibiotic resistance, with some clinical isolates having single and multidrug resistance when cultured in vitro. [62][63][64][65] Isolates have been individually resistant to tetracyclines, macrolides, fluoroquinolones, 64 or resistant to doxycycline, azithromycin, and ofloxacin. 65 In addition, a study of infected women, who completed antibiotic treatment, found that 10% of the cohort was re-infected within 1 month of treatment completion, and 13% by 3 months, even though abstinence or 100% condom use was reported.…”
Section: Treatment or Prevention?mentioning
confidence: 99%
“…[62][63][64][65] Isolates have been individually resistant to tetracyclines, macrolides, fluoroquinolones, 64 or resistant to doxycycline, azithromycin, and ofloxacin. 65 In addition, a study of infected women, who completed antibiotic treatment, found that 10% of the cohort was re-infected within 1 month of treatment completion, and 13% by 3 months, even though abstinence or 100% condom use was reported. 66 While the shortened duration of infections from early antibiotic treatment has reduced infection-associated reproductive sequelae, the number of case rates continues to increase.…”
Section: Treatment or Prevention?mentioning
confidence: 99%